Notes on birds observed on May 11 big day - Petersen, Peter C.et al (1993)
Unsigned note containing an annotated list of birds sighted on May 9 and May 11. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1993. Plustek - flatbed